Peningkatan Prestasi Belajar Siswa Melalui Penguatan Disiplin Belajar dan Dukungan Orang Tua - Mira Damayanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to investigate the effect of strengthening study discipline and parental support on students' academic achievement at SD Negeri Cengkong 1. The research method employed was a correlational survey with quantitative analysis. Data were collected from sixth-grade students through questionnaires for primary data and from students' report cards for secondary data. The research design utilized multiple regression analysis. The findings revealed a significant influence of study discipline and parental support collectively on students' academic achievement, with a 50.3% joint effect. Furthermore, both study discipline and parental support individually exhibited significant positive effects on students' academic achievement. Study discipline positively contributed to students' academic achievement, indicating that higher levels of study discipline corresponded to higher academic performance. Similarly, parental support significantly influenced students' academic achievement, suggesting that greater parental support led to better academic performance. In conclusion, this study highlights the importance of study discipline and parental support in enhancing students' academic achievement.